Selenium nano-particles as well as preparation method and application thereof
Through the preparation method combining electrochemical deposition and ultrasonic dispersion, the nanotube array and particle swarm optimization algorithm are used to achieve uniform distribution and high-quality preparation of selenium nanoparticles, solving the problems of uneven particle size and difficult to control the deposition load, and improving the reproducibility of the preparation process and the consistency of product quality.
Patent Information
- Application Number
- CN202511013247.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-23
- Publication Date
- 2025-08-22
AI Technical Summary
In the prior art, the particle size distribution of selenium nanoparticles is uneven and the deposition load is difficult to accurately control, and traditional methods are difficult to meet the requirements of high-end application fields.
Using a preparation system combining electrochemical deposition and ultrasonic dispersion, nanotube arrays are used as carriers to control the reduction and deposition of selenium nanoparticles through electrochemical deposition, and optimize ultrasonic parameters with particle swarm optimization algorithm to achieve accurate control of particle size distribution uniformity and deposition load.
The uniform distribution and high-quality preparation of selenium nanoparticles are achieved, and the problems of uneven particle size and difficult to control the deposition load are solved, which improves the reproducibility of the preparation process and the consistency of product quality.
Smart Images

Figure CN120519932A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of selenium nanoparticles, and in particular relates to selenium nanoparticles, a preparation method thereof, and applications thereof. Background Art
[0002] Selenium nanoparticles, due to their excellent biological activity and antioxidant properties, are widely used in fields such as biomedicine, catalysis, and electronic devices. Traditional selenium nanoparticle preparation techniques primarily include chemical reduction, sol-gel methods, and biosynthesis. These methods reduce selenium compounds to elemental selenium nanoparticles by adding a reducing agent to a solution or utilizing microbial metabolites. Chemical reduction methods typically employ reducing agents such as ascorbic acid, hydrazine, or sodium borohydride in aqueous or organic solvents. Biosynthesis methods utilize bioactive components from bacterial, fungal, or plant extracts to bioreduced selenium ions. Traditional preparation methods have significant drawbacks. In chemical reduction methods, the amount of reducing agent and reaction conditions are difficult to precisely control, resulting in uneven reaction rates and a wide range of selenium nanoparticle size distributions. Furthermore, residual reducing agent can affect product purity. While environmentally friendly, biosynthesis methods suffer from long reaction cycles and low yields. Furthermore, the complexity of the biological system makes precise control of the reaction mechanism difficult, resulting in poor product consistency and reproducibility. Sol-gel methods require high-temperature processing, which consumes a lot of energy, and are prone to agglomeration during the gelation process, which affects particle dispersibility. Traditional technologies make it difficult to achieve precise control of deposition load while ensuring uniformity of particle size distribution. This is because existing methods lack precise control mechanisms for the nucleation and growth processes of nanoparticles, and cannot achieve controllable point deposition on the carrier surface, resulting in the morphology and size of selenium nanoparticles being difficult to meet the stringent requirements of high-end application fields. Summary of the Invention
[0003] In view of this, the present invention provides selenium nanoparticles, a preparation method thereof, and applications thereof, which can solve the technical problems in the prior art of uneven particle size distribution and difficulty in accurately controlling the deposition load during the preparation of selenium nanoparticles.
[0004] The present invention is achieved as follows: In a first aspect, the present invention provides a selenium nanoparticle. The selenium nanoparticle is a spherical structure with a diameter of about 150 nm. The selenium element exists in the form of elemental selenium. It is prepared by electrochemical deposition on nanotube arrays followed by ultrasonic dispersion.
[0005] Wherein, the loading of the selenium nanoparticles is The selenium nanoparticles are firmly bound to the carrier and are evenly distributed in an amount of 0.3 wt % to 0.8 wt % of the weight of the nanotube array.
[0006] The second aspect of the present invention provides a method for preparing selenium nanoparticles, comprising the following steps: pre-treating pure titanium with a purity greater than 99%, soaking it in acetone and ultrasonically cleaning it to remove surface oil, and then Chemical polishing is performed in a mixed solution of solution and HF solution to remove the natural oxide film on the surface; anodizing is used to prepare the pure titanium surface after pretreatment. Nanotube arrays, anodic oxidation is carried out in a bipolar electrolytic cell with pure titanium as anode and stainless steel as cathode; electrochemical deposition is used in Selenium nanoparticles are deposited on the nanotube array, treated pure titanium is used as cathode and stainless steel is used as anode, and the electrolyte is The pH value was adjusted by dilute HF aqueous solution, and the electrochemical kinetics principle was used to describe the reduction and deposition behavior of selenium ions; the ultrasonic dispersion method was used to deposit the Selenium nanoparticles on the nanotube array were dispersed in deionized water, and the particle swarm optimization algorithm was used to optimize the ultrasonic parameter combination to obtain the best dispersion effect. The dispersed suspension was centrifuged, and the precipitate was collected and washed with deionized water. The washed selenium nanoparticles were dried in a vacuum drying oven to obtain spherical selenium nanoparticle products. A game optimization system was constructed with an upper model aiming to maximize the yield of selenium nanoparticles and a lower model aiming to minimize energy consumption.
[0007] The chemical polishing step is specifically carried out at a volume ratio of 1 to 1. Chemical polishing is performed in a mixed solution of the solution and the HF solution for 55 to 65 seconds to remove the natural oxide film on the surface, and the surface is then removed and cleaned with deionized water and dried for later use.
[0008] Wherein, the anodizing method is used to prepare The nanotube array step is as follows: the power supply is a regulated DC power supply, the voltage is controlled within the range of 18V to 25V, the oxidation time is 30 minutes to 50 minutes, and the electrolyte is an HF aqueous solution with a volume concentration of 0.4% to 0.8%.
[0009] The bipolar electrolytic cell refers to an electrolysis device having two electrodes, an anode and a cathode, and the electrode materials are pure titanium and stainless steel respectively. During the electrolysis process, ions migrate in a directional manner under the action of the electric field to form a current loop.
[0010] Among them, the Nanotube array refers to a titanium dioxide film with a regular tubular structure formed on the titanium surface by anodization. The tube diameter range is related to the anodization voltage and time, and the tube wall thickness is determined by the electrolyte concentration.
[0011] The electrochemical deposition method comprises the following steps: the electrolyte has a concentration of mol / L to In the range of mol / L The aqueous solution was prepared by adjusting the pH value to 2 to 3 using a diluted HF aqueous solution with a volume concentration of 35% to 40%. The deposition voltage was controlled in the range of 0.4V to 0.7V, and the selenium nanoparticle loading during the deposition process reached 0.5wt%.
[0012] A third aspect of the present invention provides use of the above-mentioned selenium nanoparticles in the preparation of an anti-methicillin-resistant Staphylococcus aureus drug, wherein the selenium nanoparticles are used to inhibit the growth and reproduction of methicillin-resistant Staphylococcus aureus and destroy its biofilm structure.
[0013] The antibacterial concentration range of the selenium nanoparticles is 10 μg / ml to 100 μg / ml. Within this concentration range, the selenium nanoparticles have no obvious cytotoxicity to bone marrow mesenchymal stem cells and have good biocompatibility.
[0014] The present invention solves the technical problems of uneven particle size distribution and difficulty in accurately controlling the deposition load during the preparation of selenium nanoparticles by establishing a preparation system combining electrochemical deposition and ultrasonic dispersion. The nanotube arrays act as carriers and provide regular nucleation sites for selenium nanoparticles. During the electrochemical deposition process, the voltage, electrolyte concentration, and pH value are precisely controlled to achieve the desired effect. The uniform reduction of ions on the cathode surface avoids the local concentration differences caused by the uneven distribution of reducing agents in the chemical reduction method. At the same time, the application of electrochemical kinetic principles allows the deposition process to be monitored in real time through current density, ensuring the precise control of the deposition load. Ultrasonic dispersion technology uses the cavitation effect to destroy the van der Waals force and electrostatic interaction between particles, and cooperates with the particle swarm optimization algorithm to optimize ultrasonic parameters, thereby achieving uniform dispersion of selenium nanoparticles and avoiding the agglomeration phenomenon in traditional methods. The present invention solves the technical problems of uneven particle size distribution and difficult to accurately control deposition load in the prior art because electrochemical deposition provides a controllable reduction environment. The regular structure of the nanotube array limits the disordered growth of particles, ultrasonic dispersion ensures the monodisperse state of the particles, and the multi-level synergistic control mechanism realizes the precise regulation of the selenium nanoparticle preparation process. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 TEM morphology of selenium nanoparticles.
[0016] Figure 2 The particle size distribution of selenium nanoparticles.
[0017] Figure 3 This is the XPS pattern of selenium nanoparticles.
[0018] Figure 4 Cell viability chart to evaluate the in vitro biocompatibility of selenium nanoparticles
[0019] Figure 5 Live-dead staining of bacteria to evaluate the antibacterial activity of selenium nanoparticles in vitro.
[0020] Figure 6 Crystal violet staining of bacteria to evaluate the anti-biofilm activity of selenium nanoparticles in vitro.
[0021] Figure 7 The figure is a comparison of the 14-day survival rates of mice in each experimental group.
[0022] Figure 8 The bacterial load detection chart of the organs of mice in each group on the third day after infection. DETAILED DESCRIPTION
[0023] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention.
[0024] The first aspect of the present invention provides a selenium nanoparticle, wherein the selenium nanoparticle is a spherical structure with a diameter of about 150 nm, and the selenium element exists in the form of elemental selenium. The selenium nanoparticles are prepared by electrochemical deposition on nanotube arrays and then ultrasonic dispersion. The selenium nanoparticles are firmly bound to the carrier and are evenly distributed in an amount of 0.3 wt % to 0.8 wt % of the weight of the nanotube array.
[0025] A second aspect of the present invention provides a method for preparing selenium nanoparticles, comprising the following steps: S01, pre-treat pure titanium with a purity greater than 99%, use acetone soaking and ultrasonic cleaning to remove surface oil, and then Chemical polishing is performed in a mixed solution of solution and HF solution for 55 to 65 seconds to remove the natural oxide film on the surface, and then the surface is washed with deionized water and dried for later use; S02, using anodizing method to prepare the pure titanium surface after pretreatment The nanotube array is anodized in a bipolar electrolytic cell with pure titanium as the anode and stainless steel as the cathode. The power supply is a regulated DC power supply with a voltage controlled within the range of 18V to 25V. The oxidation time is 30 minutes to 50 minutes. The electrolyte is an HF aqueous solution with a volume concentration of 0.4% to 0.8%. S03, using electrochemical deposition method Selenium nanoparticles are deposited on the nanotube array, the pure titanium treated in step S02 is used as the cathode and the stainless steel is used as the anode, and the electrolyte is a concentration of mol / L to In the range of mol / L The aqueous solution was prepared by adjusting the pH value to 2 to 3 using a diluted HF aqueous solution with a volume concentration of 35% to 40%. The deposition voltage was controlled in the range of 0.4V to 0.7V. The selenium nanoparticle loading during the deposition process reached 0.5wt%. S04, using ultrasonic dispersion method to deposit The selenium nanoparticles on the nanotube array are dispersed in deionized water, the ultrasonic frequency is set to 40 kHz to 60 kHz, the ultrasonic time is set to 20 seconds to 40 seconds, and the water bath temperature is controlled during the ultrasonic process to prevent overheating; S05. Centrifuging the dispersed suspension at a temperature of 25° C. to 30° C., a speed of 9,000 to 10,000 rpm, and a time of 10 to 15 minutes. After centrifugation, performing solid-liquid separation, collecting the precipitate, and washing it with deionized water to remove residual electrolyte and impurities. S06, drying the washed selenium nanoparticles in a vacuum drying oven, controlling the vacuum degree to be below standard atmospheric pressure during the drying process, and obtaining spherical selenium nanoparticle products after the drying is completed; S07. Conduct quality control tests on the prepared selenium nanoparticles, observe the morphology and particle size distribution using transmission electron microscopy, analyze the elemental composition and chemical state using X-ray photoelectron spectroscopy, and determine the average particle size and particle size distribution index using dynamic light scattering to ensure that the product quality meets the preset standards.
[0026] Among them, the bipolar electrolytic cell refers to an electrolysis device with two electrodes, an anode and a cathode. The electrode materials are pure titanium and stainless steel respectively. During the electrolysis process, ions migrate in a directional manner under the action of the electric field to form a current loop. Nanotube array refers to a titanium dioxide film with a regular tubular structure formed on the titanium surface by anodic oxidation. The diameter range of the tube is related to the anodic oxidation voltage and time, and the thickness of the tube wall is determined by the electrolyte concentration. Among them, electrochemical deposition refers to the formation of a titanium dioxide film in a solution under the action of an electric field. The ions undergo a reduction reaction on the cathode surface to generate elemental selenium and deposit on The deposition amount is controlled by voltage and time during the process on the surface of the nanotube array. Ultrasonic dispersion is a physical separation method that uses the cavitation effect and mechanical vibration of ultrasound to break the binding force between selenium nanoparticles and the carrier, resulting in a uniform dispersion in the solvent. The dispersion effect is determined by the ultrasound frequency and duration. Vacuum drying is a drying method that removes residual moisture and solvent from selenium nanoparticles by controlling temperature and time under reduced pressure. The vacuum environment lowers the boiling point, accelerates drying, and prevents oxidation. Transmission electron microscopy is a method that uses an electron beam to penetrate a sample to obtain morphological information. It is used to observe the spherical structure and particle size distribution of selenium nanoparticles. X-ray photoelectron spectroscopy is an analytical method that uses X-rays to excite electrons on the sample surface to obtain elemental information. It is used to confirm that selenium exists as elemental selenium. Dynamic light scattering is a method that uses laser irradiation to induce the Brownian motion of particles in a suspension to obtain particle size information. It is used to determine the average particle size and particle size distribution index.
[0027] During the electrochemical deposition process of step S03, the electrochemical kinetics principle is used to describe the reduction deposition behavior of selenium ions. The electrochemical kinetics principle is used to calculate the current density and deposition rate under different deposition conditions. The input includes deposition voltage, electrolyte concentration, temperature, pH value and electrode area. The deposition voltage is derived from the range of 0.4V to 0.7V set in step S03, and the electrolyte concentration is derived from the range of The concentration range of the aqueous solution and the temperature are derived from the ambient temperature control. The pH value is derived from the range of 2 to 3 adjusted by the HF aqueous solution in step S03. The electrode area is derived from the geometric dimensions of the pure titanium substrate. The output is the deposition amount and particle size distribution of selenium nanoparticles. The deposition amount is used to control the loading requirement of 0.5 wt% in step S03, and the particle size distribution is used to guide the expected results of the transmission electron microscopy test in step S07.
[0028] During the ultrasonic dispersion process in step S04, a particle swarm optimization algorithm is used to optimize the ultrasonic parameter combination to obtain the best dispersion effect. The particle swarm optimization algorithm is used to find the optimal combination of ultrasonic frequency, ultrasonic time, ultrasonic power and temperature. The input includes the ultrasonic frequency range, time range, power range, temperature range and dispersion uniformity target value. The ultrasonic frequency range is derived from 40kHz to 60kHz set in step S04, the time range is derived from 20 seconds to 40 seconds set in step S04, the power range is derived from the technical parameters of the ultrasonic equipment, the temperature range is derived from 25°C to 30°C set in step S04, and the dispersion uniformity target value is derived from the standard requirements of the dynamic light scattering measurement in step S07. The output is the optimal ultrasonic parameter combination and the expected dispersion uniformity index. The optimal ultrasonic parameter combination is used to guide the selection of specific operating parameters in step S04, and the dispersion uniformity index is used to evaluate the effect of centrifugal separation in step S05.
[0029] A game optimization system is constructed with an upper model that aims to maximize the yield of selenium nanoparticles and a lower model that aims to minimize energy consumption. The upper objective function is used to maximize the yield and quality of selenium nanoparticles under given energy consumption constraints. The input includes deposition voltage, deposition time, electrolyte concentration, temperature and energy consumption parameters output by the lower model. The deposition voltage comes from the voltage range set in step S03, the deposition time comes from the process time in step S03, and the electrolyte concentration comes from the temperature in step S03. The concentration of the aqueous solution is set, the temperature is derived from the temperature control range in step S04, the energy consumption parameters are derived from the calculation output of the lower model, the output is the optimal process parameter combination and the expected output, the optimal process parameter combination is used to guide the specific operating conditions of steps S02 and S03, the expected output is used to evaluate the economic benefits of the entire preparation method, the lower objective function is used to minimize the total energy consumption of the entire preparation process while meeting the output requirements, the input includes equipment power, operating time, cooling system energy consumption, vacuum pump energy consumption and process parameters of the upper model, the equipment power is derived from the rated power of the electrolytic cell and ultrasonic equipment, the operating time is derived from the cumulative time of steps S02 to S06, the cooling system energy consumption is derived from the cooling requirement of temperature control in step S04, the vacuum pump energy consumption is derived from the energy consumption requirement of vacuum drying in step S06, the process parameters are derived from the output results of the upper model, the output is the optimal equipment operation strategy and the minimum energy consumption value, the optimal equipment operation strategy is used to guide the energy management of the entire preparation process, and the minimum energy consumption value is used to evaluate the energy efficiency and environmental impact of the preparation method.
[0030] A third aspect of the present invention provides the use of selenium nanoparticles in the preparation of an anti-methicillin-resistant Staphylococcus aureus drug. The selenium nanoparticles are used to inhibit the growth and reproduction of methicillin-resistant Staphylococcus aureus and destroy its biofilm structure. The selenium nanoparticles have an antibacterial concentration range of 10 μg / ml to 100 μg / ml, exhibit no significant cytotoxicity to bone marrow mesenchymal stem cells within this concentration range, and exhibit good biocompatibility.
[0031] The specific implementation of the preparation method provided by the second aspect of the present invention is described in detail below.
[0032] The specific implementation method of step S01 is to pre-treat the pure titanium substrate using multi-stage cleaning and surface modification technology. First, the pure titanium substrate with a purity greater than 99% is immersed in an acetone solution. The volume of the acetone solution should be sufficient to completely immerse the surface of the titanium substrate. The immersion time is controlled within the range of 10 to 15 minutes. At the same time, ultrasonic waves with a frequency of 25 to 35 kHz are applied for auxiliary cleaning, and the ultrasonic power density is controlled at 2 to 4 watts per square centimeter. The purpose of this process is to use the strong polar solvent properties of acetone and the cavitation effect of ultrasonic waves to remove organic oil stains and machining residues on the titanium surface. Subsequently, chemical polishing is carried out. The cleaned titanium substrate is placed in a mixture of nitric acid solution and hydrofluoric acid solution in a volume ratio of 1:1. The concentration of nitric acid is controlled at 65% to 70%, and the concentration of hydrofluoric acid is controlled at 40% to 48%. The polishing time is precisely controlled between 55 seconds and 65 seconds. This process uses the synergistic effect of the strong oxidizing effect of nitric acid and the strong corrosive effect of hydrofluoric acid on oxides to effectively remove the natural oxide film and microscopic unevenness on the titanium surface. The polishing liquid temperature is maintained at 20°C to 25°C to control the reaction rate. After completing chemical polishing, it is immediately rinsed with deionized water multiple times. The conductivity of the rinse water should be less than 10 microSiemens per centimeter. The rinse time is not less than 5 minutes to ensure that the residual acidic substances on the surface are completely removed. Finally, it is dried in a clean environment. The drying temperature is controlled at 25°C to 30°C and the relative humidity is controlled at 40% to 60%.
[0033] The specific implementation of step S02 is to use the voltage controlled anodic oxidation technology to prepare the ordered Nanotube array structure, this step is based on Faraday's law of electrolysis and the principle of electrochemical kinetics to achieve orderly oxidation of titanium. Pretreated pure titanium is used as the anode and stainless steel is used as the cathode. The distance between the two electrodes is controlled at 2 to 5 cm, and the electrolytic cell is made of polytetrafluoroethylene to avoid interference from impurity ions. The electrolyte is a hydrofluoric acid aqueous solution, and the volume concentration is precisely controlled in the range of 0.4% to 0.8%. The concentration of hydrofluoric acid directly affects the diameter and wall thickness of the nanotubes. A lower concentration is conducive to the formation of a regular tubular structure. The anodic oxidation voltage is provided by a regulated DC power supply, and the voltage range is set to 18 volts to 25 volts. The voltage determines the length and diameter of the nanotubes. Too low a voltage will lead to insufficient oxidation, and too high a voltage will cause the tube wall to collapse. The oxidation time is controlled at 30 minutes to 50 minutes. During the oxidation process, the current density will show a trend of first increasing and then decreasing. When the current density is stable at 0.5 to 1.0 amperes per square decimeter, it indicates that the nanotube array is fully formed. The electrolyte temperature is maintained between 15°C and 25°C throughout the process. Excessively high temperatures accelerate the volatilization of hydrofluoric acid and affect the order of the nanotube array. After oxidation, the remaining electrolyte is rinsed with deionized water and then dried at 80°C to 100°C for 30 minutes to stabilize the nanotube structure.
[0034] The specific implementation of step S03 is to use the potential-controlled electrochemical deposition technology to Selenium nanoparticles are deposited on the surface of the nanotube array. This process is based on the principle of electrochemical kinetics and Faraday's law to achieve the directional reduction of selenium ions. The titanium substrate of the nanotube array serves as the cathode, stainless steel serves as the anode, and the electrode configuration adopts a three-electrode system and introduces a saturated calomel electrode as a reference electrode to accurately control the deposition potential. The electrolyte uses a sodium selenite aqueous solution with a concentration range of mole per liter The concentration of sodium selenite directly affects the deposition rate and particle size distribution of selenium nanoparticles. A dilute hydrofluoric acid aqueous solution with a volume concentration of 35% to 40% is used to adjust the pH of the electrolyte and accurately control the pH value within the range of 2 to 3. The acidic environment is conducive to The deposition voltage is controlled by an electrochemical workstation and the voltage range is set to 0.4V to 0.7V. This voltage range is determined based on the standard electrode potential of selenium and can ensure The ions undergo a reduction reaction on the cathode surface to produce elemental selenium. The deposition process utilizes an electrochemical kinetic control strategy combining cyclic voltammetry and chronoamperometry. The progress of the deposition process is assessed by monitoring changes in current density. Deposition is terminated when the selenium nanoparticle loading reaches 0.5%, which is calculated using coulometric methods. The electrolyte temperature is maintained between 25°C and 30°C throughout the deposition process, and magnetic stirring is used to maintain solution homogeneity.
[0035] The specific implementation of step S04 is to use the ultrasonic dispersion technology guided by the particle swarm optimization algorithm to disperse the selenium nanoparticles from The nanotube array is separated and evenly dispersed on the carrier. This step is based on the ultrasonic cavitation effect and the particle swarm intelligent optimization principle to achieve the best dispersion effect. First, a particle swarm optimization algorithm model is established, with dispersion uniformity as the objective function and ultrasonic frequency, ultrasonic time, ultrasonic power and water bath temperature as optimization variables. The ultrasonic frequency search range is set to 40 kHz to 60 kHz. This frequency range can produce a suitable cavitation bubble size to destroy the binding force between the nanoparticles and the carrier. The ultrasonic time search range is set to 20 seconds to 40 seconds. If the time is too short, it cannot be fully dispersed, and if the time is too long, the nanoparticles will re-agglomerate. The particle swarm size in the algorithm is set to 20 to 30 particles, the maximum number of iterations is set to 50 to 100 times, the inertia weight is reduced from 0.9 to 0.4 using a linear decreasing strategy, and the acceleration factor is set to 2.0. During the optimization process, the polydispersity index measured by dynamic light scattering is used as the fitness function, and the target value is set to less than 0.3 to ensure good dispersion uniformity. The titanium nanotube array substrate was placed in deionized water, with the water volume being 10 to 20 times that of the substrate to provide ample dispersion space. The ultrasonic equipment was set up according to the optimal parameter combination output by the particle swarm optimization algorithm. A water bath was used to control the sonication process. The water bath temperature was controlled based on the optimization results but not to exceed 35°C to prevent nanoparticle oxidation. The ultrasonic dispersion process was paused for 2 to 3 seconds every 5 to 10 seconds to avoid local overheating. The dispersion effect was evaluated in real time using an online particle size monitoring system.
[0036] The specific implementation of step S05 is to use gradient centrifugation technology to perform solid-liquid separation and purification on the dispersed selenium nanoparticle suspension. This process effectively separates particles of different particle sizes based on the principle of particle sedimentation dynamics in a centrifugal field. The centrifugation is performed using a high-speed refrigerated centrifuge, and an angle rotor is selected to improve separation efficiency. The centrifugation conditions are set at a temperature of 25°C to 30°C, a speed of 9000 to 10000 rpm, and a centrifugation time of 10 to 15 minutes. This parameter combination is determined based on Stokes' sedimentation law and can ensure complete sedimentation of the nanoparticles and avoid particle damage caused by excessive centrifugation. The centrifugation process is divided into two stages: primary separation and fine separation. The primary separation is performed at a relatively low speed of 8000 rpm for 5 minutes to remove large impurities and undispersed agglomerates. The fine separation is performed at a set speed for the full time to collect selenium nanoparticles within the target particle size range. After centrifugation, the supernatant is carefully removed and the sediment at the bottom of the tube is collected. The sediment is the separated selenium nanoparticles. The precipitate is then washed and purified. The precipitate is redispersed with deionized water at a volume of 50% to 70% of the original suspension volume. Gently agitate to redisperse the particles, then centrifuge again. Repeat the washing process two to three times until the supernatant conductivity is less than 20 microsiemens per centimeter, ensuring that residual electrolyte and process impurities are completely removed. The pH of the supernatant is tested after each wash; a near-neutral pH indicates adequate washing.
[0037] Step S06 utilizes vacuum freeze-drying to remove residual moisture from the selenium nanoparticles while preserving their morphology. This process utilizes the principle of water sublimation in a vacuum environment to achieve low-temperature dehydration. The washed wet selenium nanoparticles are transferred to a vacuum drying oven and spread in a thin layer on a polytetrafluoroethylene tray, with a thickness of 2 to 5 mm to ensure uniform drying. The vacuum level in the vacuum drying oven is controlled below standard atmospheric pressure, specifically between 1 and 10 Pascals, which significantly lowers the boiling point of water and accelerates the dehydration process. The drying temperature is programmed, initially at 25°C for one hour to prevent rapid dehydration-induced particle deformation. The temperature is then slowly raised to 45°C to 55°C and maintained for four to six hours to complete the primary dehydration process. Dehydration progress is monitored gravimetrically throughout the drying process; drying is complete when the difference between two consecutive weighings is less than 0.1% of the total sample weight. During the drying process, a cold trap is placed at the front of the vacuum pump to collect water vapor to protect the vacuum system. The cold trap temperature is controlled between -20°C and -30°C. After drying, slowly introduce dry nitrogen to restore atmospheric pressure. The aeration rate is controlled at 50 to 100 ml per minute to prevent airflow from disrupting the particle structure. The resulting product is a free-flowing, spherical selenium nanoparticle powder with a moisture content of less than 1%.
[0038] The specific implementation method of step S07 is to use a multivariate characterization technology to conduct a comprehensive quality control test on the prepared selenium nanoparticles. This step is based on the principle of complementarity of different characterization technologies to achieve an accurate assessment of product quality. Transmission electron microscopy detection uses a transmission electron microscope with an accelerating voltage of 200 kilovolts. The sample is prepared by drop coating the nanoparticle dispersion onto a copper mesh grid. The concentration of the dispersion is controlled at 0.1 to 0.5 mg per milliliter to obtain a suitable particle density, and then observed after drying. The morphological information and high-resolution structural images of the nanoparticles are obtained by transmission electron microscopy, and the particle size data of no less than 200 particles are measured and statistically analyzed. The average particle size and the standard deviation of the particle size distribution are calculated. The standard deviation of the particle size distribution of qualified products should be less than 20% of the average particle size. X-ray photoelectron spectroscopy (XPS) uses a monochromatized aluminum target X-ray source with an X-ray power setting of 200 to 300 watts. The chemical state of selenium is determined by scanning the binding energy range of selenium. The peak in the 2p orbital binding energy of selenium should appear in the range of 55 to 56 electron volts, indicating the presence of elemental selenium. The characteristic peak of selenium oxide should be absent in the spectrum to ensure product purity. Dynamic light scattering (DLS) uses a helium-neon laser with a wavelength of 632.8 nanometers and a scattering angle of 90 degrees. The sample is dispersed in deionized water to a concentration of 0.01 to 0.1 mg / mL. The measurement temperature is controlled at 25°C, and five replicates are measured for each sample, with the average value taken as the average. Dynamic light scattering determines the hydrodynamic diameter and polydispersity index of the particles. Acceptable products should have a polydispersity index of less than 0.3, and the average particle size should be within the design target range and consistent with transmission electron microscopy results. Quality control standards require all test results to meet pre-set specifications, with product purity exceeding 95%, uniform particle size distribution, and a regular spherical morphology.
[0039] It should be noted that the first and most critical technical idea of the present invention is to use the principle of electrochemical kinetics to accurately describe and control the reduction deposition behavior of selenium ions. Traditional electrochemical deposition methods often rely on empirical parameter settings, and lack in-depth understanding and precise control of ion transport, electrode reaction kinetics and interface phenomena during the deposition process. By introducing the principle of electrochemical kinetics, the present invention can analyze the current density distribution and deposition rate variation under different deposition conditions from a theoretical level, and achieve accurate prediction and regulation of the reduction reaction process of selenium ions on the surface of TiO2 nanotube arrays. This deposition process control method based on theoretical guidance can significantly improve the deposition uniformity and controllability of particle size distribution of selenium nanoparticles, while avoiding the problems of uneven deposition, particle agglomeration and irregular morphology caused by improper parameter settings in traditional methods.
[0040] The second most critical technical idea of the present invention is to use the particle swarm optimization algorithm to intelligently optimize the combination of ultrasonic dispersion parameters. Traditional ultrasonic dispersion processes usually use fixed parameters or simple parameter scanning methods, which makes it difficult to find the optimal matching relationship between multiple parameters, and often lead to insufficient dispersion or excessive dispersion leading to particle breakage. By introducing the particle swarm optimization algorithm, the present invention can intelligently search for the optimal combination of ultrasonic frequency, time, power and temperature in the multidimensional parameter space to achieve global optimization of the dispersion effect. This intelligent optimization method can not only overcome the blindness and limitations of parameter selection in traditional methods, but also adaptively adjust the parameter combination according to different dispersion uniformity target values, ensuring the complete detachment of selenium nanoparticles from the carrier surface and uniform dispersion in the solution.
[0041] The synergistic effect of these two key technical ideas has produced significant comprehensive technical advantages. Precise deposition guided by the principles of electrochemical kinetics provides an ideal particle carrier structure and suitable particle-carrier bonding strength for subsequent ultrasonic dispersion, while the ultrasonic dispersion parameters optimized by the particle swarm optimization algorithm can fully utilize the advantages of high-quality particles produced by electrochemical deposition. The organic combination of the two realizes the optimization control of the entire process from particle generation to particle separation, which not only ensures the high-quality preparation of selenium nanoparticles, but also significantly improves the reproducibility of the preparation process and the consistency of product quality, fundamentally solving the technical problems of poor process stability and large fluctuations in product quality in traditional methods.
[0042] The use of selenium nanoparticles provided in the third aspect of the present invention in preparing a drug against methicillin-resistant Staphylococcus aureus is described in detail as follows.
[0043] The spherical selenium nanoparticles prepared by the present invention are used as active ingredients, and first of all, they need to be subjected to appropriate surface modification and stabilization treatment. The prepared selenium nanoparticles are dispersed in physiological saline under sterile conditions, and the surface of the selenium nanoparticles is coated and modified by adding an appropriate amount of biocompatible surfactant such as polyethylene glycol or chitosan, which can not only maintain its antibacterial activity but also improve its stability and biocompatibility in a physiological environment. The modified selenium nanoparticle suspension is ultrasonically treated to ensure uniform dispersion to avoid reduced activity caused by particle aggregation. According to clinical application requirements, selenium nanoparticles can be prepared into various dosage forms such as injections, topical gels or sprays with different concentrations, wherein the injection concentration is usually controlled within the range of 10-100 micrograms per milliliter, and the concentration of topical preparations can be appropriately increased to 100-500 micrograms per milliliter.
[0044] The antibacterial mechanism of selenium nanoparticles against methicillin-resistant Staphylococcus aureus is primarily based on their unique oxidative stress-inducing and cell membrane-disrupting effects. When selenium nanoparticles come into contact with MRSA bacteria, the selenium atoms on the particle surface catalyze the production of reactive oxygen species within the bacterial cells, including superoxide anions, hydroxyl radicals, and hydrogen peroxide. These reactive oxygen species attack the bacterial cell membrane lipid bilayer, disrupting the integrity of the membrane structure and ultimately causing bacterial death. Selenium nanoparticles can also interfere with the electron transfer process in the bacterial respiratory chain, inhibiting ATP synthesis and fundamentally disrupting the bacterial energy metabolism system. In terms of efficacy evaluation, the minimum inhibitory concentration and minimum bactericidal concentration of selenium nanoparticles against MRSA can be determined through standard antimicrobial susceptibility testing. Time-kill curves are also used to analyze the bactericidal kinetics to ensure that the drug can achieve effective antibacterial effects in clinical applications.
[0045] A key characteristic of MRSA infection is its robust biofilm formation. This biofilm structure provides a natural protective barrier for bacteria, contributing to the difficulty in curing the infection and the further development of antibiotic resistance. Selenium nanoparticles exhibit unique advantages in combating biofilms. Their small size enables them to penetrate deep into the biofilm structure and directly target bacterial cells within it. Selenium nanoparticles can interfere with bacterial exopolysaccharide and protein synthesis, disrupting the biofilm matrix. They also kill dormant bacteria within the biofilm by producing reactive oxygen species, effectively inhibiting biofilm formation and progression. In clinical application, selenium nanoparticle formulations can be used to treat a variety of infections caused by MRSA, including skin and soft tissue infections, wound infections, and medical device-related infections. For superficial infections, topical administration can be used directly at the site of infection. For deep or systemic infections, intravenous administration can be considered, but the dosage and frequency of administration must be carefully controlled to ensure effective antimicrobial effects while avoiding systemic toxicity.
[0046] In the drug development process, the safety evaluation of selenium nanoparticles is a crucial link. Since the therapeutic window of selenium is relatively narrow, the safety characteristics of selenium nanoparticles need to be comprehensively evaluated through cytotoxicity tests, acute toxicity tests and long-term toxicity tests. In vitro cytotoxicity tests should be evaluated using a variety of cell lines including normal human cells and tumor cells to determine the maximum tolerated concentration for normal cells. Animal experiments should include single-dose toxicity tests and repeated-dose toxicity tests to observe the distribution, metabolism and excretion of selenium nanoparticles in the body and evaluate their potential toxic effects on important organs such as the liver and kidneys. In terms of quality control, it is necessary to establish a complete characterization and detection method for selenium nanoparticles, including detection standards for key quality indicators such as particle size distribution, morphology and structure, selenium content, and dispersion stability, to ensure the quality consistency and controllability of each batch of products and provide reliable guarantees for safe and effective clinical applications.
[0047] Specifically, the principle of the present invention is: the principle of the technical solution of the present invention to solve the above technical problems lies in constructing a preparation system for multi-scale coordinated regulation. Nanotube arrays are formed on the surface of titanium substrates by anodic oxidation. The geometric confinement effect of the tubular structure provides a spatially confined environment for the nucleation of selenium nanoparticles. The controllability of the tube diameter and length ensures the consistency of the carrier structure. The ions migrate toward the cathode, and a reduction reaction occurs at the electrode interface to generate elemental selenium. The electrochemical kinetics principle describes the kinetic behavior of the electrode reaction through the Butler-Volmer equation, and the relationship between the output current density and the deposition rate is used to achieve quantitative control of the deposition process.
[0048] Precise control of the deposition voltage determines the overpotential at the electrode interface, which directly affects the nucleation driving force and nucleation density. A lower overpotential favors the formation of uniform nucleation sites, avoiding explosive nucleation caused by localized high concentrations. The electrolyte pH is adjusted to an acidic range of 2 to 3 using hydrofluoric acid. This acidic environment suppresses the hydrolysis side reaction of selenium ions and improves the selectivity of electrochemical reduction. The concentration is controlled at to mol / L range, ensuring sufficient reactant supply while avoiding mass transfer limitations.
[0049] The ultrasonic dispersion process uses a particle swarm optimization algorithm to find the optimal parameter combination. This algorithm simulates the foraging behavior of bird flocks and searches for the global optimal solution in a multidimensional parameter space. The position of a particle in the solution space represents the ultrasonic parameter combination, while its velocity represents the direction of parameter adjustment. Parameter optimization is achieved by sharing information about individual and group optimality. The cavitation effect of ultrasound generates microjets and shock waves, which mechanically disrupt the aggregated structure between particles. The frequency is controlled within the 40 to 60 kHz range, ensuring a balance between cavitation intensity and dispersion effectiveness.
[0050] A two-level game optimization system achieves multi-objective optimization of the preparation process by coupling an upper-level yield maximization model with a lower-level energy consumption minimization model. The upper-level model uses selenium nanoparticle yield and quality as objective functions, with constraints including equipment capacity and process window. The lower-level model uses total energy consumption as an objective function, with constraints including production requirements and equipment operating limits. The game equilibrium solution corresponds to the optimal operating state of the system, ensuring a balance between economic and technical performance during the preparation process.
[0051] A specific embodiment 1 of the present invention is provided below. The specific implementation of each step in this embodiment 1 is described in detail as follows.
[0052] The specific implementation of step S01 is the same as above and will not be described in detail here.
[0053] The specific implementation of step S02 is to use the voltage-controlled anodic oxidation technology based on Faraday's law of electrolysis to prepare an ordered Nanotube array structure. According to Faraday's law of electrolysis, the amount of charge transferred during the electrolysis process is directly related to the degree of oxidation, as shown below: ; Where, is the total charge in coulombs; is the electron transfer number, for the oxidation reaction of titanium ; is the Faraday constant, Coulomb per mole; is the molar number of titanium atoms participating in the reaction.
[0054] The geometric parameters of the nanotube array are calculated using the electrochemical kinetic equation, which is expressed as follows: ; Where, is the inner diameter of the nanotube, in nanometers; is the geometric factor, which is obtained by measuring the tube diameter under different conditions through scanning electron microscopy and fitting, and its value range is 0.8-1.2; is the anodic oxidation voltage, ranging from 18 to 25 volts; is the oxidation time, ranging from 30 to 50 minutes; is the concentration of hydrofluoric acid, ranging from 0.4% to 0.8%.
[0055] The variation of current density is described by the time-dependent electrochemical kinetic equation, which is specifically expressed as follows: ; Where, For the moment The current density is in amperes per square decimeter; is the initial current density; is the time constant, ranging from 5 to 15 minutes; is the steady-state current density, ranging from 0.5 to 1.0 amperes per square decimeter.
[0056] The specific implementation of step S03 is to use the potential-controlled electrochemical deposition technology based on the electrochemical kinetics principle. Selenium nanoparticles are deposited on the surface of the nanotube array. The reduction deposition process of selenium ions follows the Butler-Volmer equation, which is specifically expressed as follows: ; Where, is the current density in amperes per square meter; is the exchange current density, measured by the Tafel slope method, with a typical value of to Ampere per square meter; is the transfer coefficient, which is 0.5; is the electron transfer number, for the selenium reduction reaction ; is the Faraday constant; is the overpotential in volts; is the gas constant, Joule per mole per Kelvin; It is absolute temperature, ranging from 298 to 303 Kelvin.
[0057] The deposition amount of selenium nanoparticles was calculated by coulometric method, which is specifically expressed as follows: ; Where, is the mass of selenium deposited, in grams; is the molar mass of selenium, Grams per mole; is the deposition current in amperes; is the deposition time in seconds.
[0058] The deposition rate of selenium nanoparticles is calculated using differential form, as shown below: ; Where, is the deposition rate in grams per second.
[0059] When the selenium nanoparticle loading reaches 0.5%, the stopping condition is determined by the mass fraction calculation formula, which is specifically expressed as follows: ; Where, is the mass fraction of selenium; is the mass of the matrix in grams.
[0060] The specific implementation of step S04 is to use ultrasonic dispersion technology guided by particle swarm optimization algorithm. The objective function of the particle swarm optimization algorithm takes dispersion uniformity as the optimization goal, which is specifically expressed as follows: ; Where, is the objective function; is the polydispersity index, with a target value of less than 0.3.
[0061] The particle position update equation is specifically expressed as follows: ; Where, For the The particle in The position vector of the iteration; For the The particle in The position vector of the iteration; For the The particle in The velocity vector for the iteration.
[0062] The particle velocity update equation is expressed as follows: ; Where, is the inertia weight, which decreases linearly from 0.9 to 0.4; and is the acceleration factor, all set to 2.0; and A random number between 0 and 1; For the The historical optimal position of a particle; is the global optimal position.
[0063] The dispersion force calculation of ultrasonic cavitation effect is specifically expressed as follows: ; Where, is the cavitation dispersion force, in Newton; is the cavitation coefficient, which is obtained by measuring the dispersion effect under different ultrasonic conditions through laser particle size analyzer and fitting, and the value range is 1.2-2.0; is the ultrasonic power in watts; It is the ultrasonic frequency, ranging from 40 to 60 kHz; is the ultrasound time, ranging from 20 to 40 seconds.
[0064] The specific implementation of step S05 is to use gradient centrifugation technology to perform solid-liquid separation based on Stokes' sedimentation law. The sedimentation velocity of the nanoparticles in the centrifugal field is calculated using the modified Stokes equation, which is specifically expressed as follows: ; Where, is the sedimentation velocity in meters per second; is the particle radius in meters; is the particle density, the density of selenium is 4790 kg per cubic meter; is the fluid density, the density of water is 1000 kg per cubic meter; is the effective acceleration due to gravity; is the dynamic viscosity of the fluid, water at 25°C is Pascal second.
[0065] The calculation of effective gravitational acceleration in the centrifugal field is expressed as follows: ; Where, is the angular velocity in radians per second; is the centrifugal radius in meters.
[0066] The relationship between angular velocity and rotational speed is expressed as follows: ; Where, is the rotational speed, ranging from 9000 to 10000 revolutions per minute.
[0067] The centrifugal separation time is calculated by the sedimentation distance, which is specifically expressed as follows: ; Where, is the separation time in seconds; is the settlement distance in meters.
[0068] The specific implementation of step S06 is the same as above and will not be described in detail here.
[0069] The specific implementation of step S07 is to use multivariate characterization technology to perform quality control testing. The statistical analysis of particle size distribution is described by the normal distribution function, which is specifically expressed as follows: ; Where, is the particle size distribution density function; is the particle diameter in nanometers; is the average particle size in nanometers; is the standard deviation in nanometers.
[0070] The calculation of the polydispersity index is as follows: ; In the formula, the qualified product The value should be less than 0.3.
[0071] The upper objective function of the game optimization system aims to maximize the yield of selenium nanoparticles, which is specifically expressed as follows: ; Where, is the upper layer objective function value; is the yield indicator; is a quality indicator; The total energy consumption output by the lower model; and is the weight coefficient; is the energy consumption constraint Lagrange multiplier.
[0072] The lower objective function aims to minimize energy consumption, which is specifically expressed as follows: ; Where, is the energy consumption of the electrolysis process; is the energy consumption of the ultrasonic process; is the energy consumption of the centrifugal process; is the energy consumption of vacuum drying, and the unit is kilowatt-hour.
[0073] The calculation formula for each energy consumption is: ; ; ; ; In the formula, each power and time parameter corresponds to the rated power and operating time of the corresponding equipment respectively.
[0074] In order to better understand and implement the present invention, the following provides an example 2 of a specific application scenario of selenium nanoparticles (SeNPs) of the present invention: Example: Preparation, Characterization and Biological Performance Evaluation of Selenium Nanoparticles
[0075] In order to fully characterize the physical and chemical properties and biological performance of the prepared selenium nanoparticles, transmission electron microscopy (TEM) was used to observe the microscopic morphological characteristics of the selenium nanoparticles. During the experiment, the freshly prepared selenium nanoparticle suspension was diluted with deionized water to an appropriate concentration of about 0.1 mg / mL, and then 10 μL of the diluted sample was added dropwise to a pre-prepared carbon film-covered copper grid. To avoid sample agglomeration during the drying process, the copper grid containing the sample was placed at room temperature and dried naturally for about 30 minutes to ensure that the water was completely evaporated. After drying, the sample was transferred to a transmission electron microscope for observation, the acceleration voltage was set to 200 kV, and different magnifications were selected for image acquisition and analysis. Through TEM observation, it was found that Figure 1As shown, the prepared selenium nanoparticles exhibit a very regular spherical morphology, with clear and sharp particle boundaries, a smooth surface, and no obvious defects or irregular protrusions. Notably, these selenium nanoparticles appear well-dispersed in the TEM field of view, with relatively uniform distances between particles and no obvious agglomeration or aggregation, indicating that the preparation process parameters have been well optimized and controlled. High-magnification observations reveal that the selenium nanoparticles are quite uniform in size and highly regular in shape. This uniform spherical structure not only facilitates their stable dispersion in solution but also lays a good foundation for their subsequent biological applications.
[0076] In order to accurately determine the particle size distribution characteristics of selenium nanoparticles, dynamic light scattering technology was used for quantitative analysis. Before the experiment, the selenium nanoparticle suspension was ultrasonically dispersed in an ultrasonic cleaner with a power of 100W for 15 minutes to ensure that the particles were fully dispersed and to avoid agglomeration that affected the measurement accuracy. The sample was then transferred to a cuvette and subjected to dynamic light scattering measurement at a constant temperature of 25°C. The laser scattering angle was set to 90°, the data acquisition time was 120 seconds, and each sample was measured 5 times to ensure the reliability and reproducibility of the results. The scattering intensity changes of the sample were monitored during the measurement, and the hydrodynamic diameter of the particles was calculated by analyzing the fluctuations in the scattered light intensity caused by Brownian motion. The results of dynamic light scattering analysis showed that Figure 2 As shown, the average hydrodynamic diameter of the selenium nanoparticles is approximately 150 nm, and the particle size distribution curve exhibits a typical unimodal distribution with a sharp and symmetrical peak. The polydispersity index (PDI) value is 0.26, well below the threshold of 0.5, demonstrating the excellent monodispersity and uniform size distribution of the prepared selenium nanoparticles. This narrow size distribution is important for ensuring the consistent and predictable behavior of selenium nanoparticles in biological systems.
[0077] In order to determine the elemental composition of selenium nanoparticles and the specific chemical valence state of selenium, X-ray photoelectron spectroscopy was used for in-depth surface chemical analysis. Before the experiment, the selenium nanoparticle suspension was centrifuged and washed multiple times to remove organic molecules and impurity ions on the surface, and then dried in a vacuum drying oven at 60°C for 12 hours to obtain dry selenium nanoparticle powder. The powder sample was evenly spread on a standard sample table to ensure that the sample surface was flat and the thickness was moderate. The XPS test was carried out in an ultra-high vacuum environment with a vacuum degree better than 1×10⁻ 9Pa, using monochromated Al Kα rays as the excitation source, and the X-ray power was set to 150W. First, a full spectrum scan was performed to obtain the overall elemental composition information of the sample, with a scanning range of 0-1200eV and an energy step of 1.0eV. Subsequently, a high-resolution fine scan was performed on the 3d orbital of selenium, with a scanning range of 50-65eV and an energy step reduced to 0.1eV to obtain higher energy resolution. Through careful analysis and peak position fitting of the XPS spectrum, it was found that the binding energy of selenium 3d5 / 2 was at 55.2eV, and the binding energy of selenium 3d3 / 2 was at 56.0eV, as shown in Figure 2. Figure 3 As shown, these binding energy values are consistent with the standard data for elemental selenium reported in the literature. Furthermore, no characteristic peaks of selenium oxides were detected in the higher binding energy region, confirming that the prepared nanoparticles are indeed pure elemental selenium, with the selenium element maintaining its zero valence state and no oxidation reaction occurring.
[0078] In terms of biosafety evaluation, bone marrow mesenchymal stem cells were selected as a cell model to evaluate the potential cytotoxicity of selenium nanoparticles. BMSCs cell culture was carried out under strict sterile conditions, and the culture medium was DMEM complete medium, to which 10% heat-inactivated fetal bovine serum (originating in New Zealand, the batch number passed the endotoxin test), 100U / mL penicillin and 100μg / mL streptomycin were added. The cells were maintained in a cell culture incubator at 37°C, 5% CO2, and 95% relative humidity, and passaged every 2-3 days to maintain cell viability. When conducting cytotoxicity experiments, BMSCs cells were cultured at a rate of 1×10 4 The cells were seeded at a density of 100 cells / well in a 96-well cell culture plate, and 100 μL of complete culture medium was added to each well. The cells were cultured in an incubator for 24 hours to allow the cells to fully adhere to the wall. Subsequently, a series of selenium nanoparticle suspensions were prepared, with the concentration gradient set to 5, 10, 25, 50, 100, and 200 μg / mL. Six parallel wells were set for each concentration to ensure the statistical significance of the data. At the same time, a blank control group (containing only culture medium) and a negative control group (cells without selenium nanoparticles) were set up. After the selenium nanoparticle suspension was added to the corresponding wells, the culture was continued for 24 hours and 48 hours. At the predetermined time point, the MTT colorimetric method was used to detect cell viability. 20 μL of MTT solution (5 mg / mL) was added to each well. After continuing to culture for 4 hours, the supernatant was discarded, 150 μL of DMSO was added to dissolve the formazan crystals, and the absorbance value was measured at a wavelength of 570 nm using an enzyme marker. The experimental results showed that, Figure 4 As shown in the data, selenium nanoparticles did not exhibit obvious cytotoxic effects on BMSCs cells within all tested concentration ranges. Even at the highest tested concentration of 200 μg / mL, the cell viability was still maintained at more than 90% of that of the control group, indicating that the prepared selenium nanoparticles have good cell compatibility and biosafety.
[0079] In the antibacterial performance evaluation experiment, methicillin-resistant Staphylococcus aureus, a common clinical pathogen, was selected as a representative pathogenic strain for antibacterial activity testing. First, the MRSA strain was removed from the -80°C freezer and revived on a blood plate for 24 hours. A single colony was picked and inoculated into LB broth medium and cultured at 37°C with shaking until the logarithmic growth phase. The bacterial concentration was adjusted to 1×10 by measuring the optical density of the bacterial solution and combining it with the standard curve. 6 CFU / mL. The bacterial suspension with adjusted concentration was mixed with selenium nanoparticles of different concentrations and co-cultured at 37°C for 2 hours. In order to visually observe the effect of selenium nanoparticles on bacterial viability, the LIVE / DEAD BacLight bacterial live-dead staining kit was used for fluorescent staining. The kit contains SYTO 9 green fluorescent dye and propidium iodide red fluorescent dye. SYTO 9 can penetrate the cell membranes of all bacteria and bind to DNA to emit green fluorescence, while propidium iodide can only penetrate the damaged cell membranes and enter the dead bacteria to emit red fluorescence. After the staining is completed, a fluorescence microscope is used to observe and capture images at the corresponding excitation and emission wavelengths. The results of fluorescence microscopy observation clearly show that, Figure 5 As shown in the figure, with the gradual increase in the concentration of selenium nanoparticles, the proportion of red fluorescence (representing dead bacteria) in the field of view increased significantly, while the green fluorescence (representing live bacteria) decreased accordingly, which intuitively confirmed that selenium nanoparticles have a concentration-dependent bactericidal effect on MRSA.
[0080] At the same time, in order to evaluate the inhibitory effect of selenium nanoparticles on bacterial biofilm formation, the classic crystal violet staining method was used for quantitative detection. 5 CFU / mL) was inoculated into a 96-well polystyrene microplate, 200 μL per well, and different concentrations of selenium nanoparticles were added at the same time, with a concentration gradient of 12.5, 25, 50, and 100 μg / mL. The microplate was placed at 37°C for 24 hours without shaking to facilitate the formation of biofilms. After the culture, the supernatant was carefully discarded, and the plate was gently rinsed 3 times with PBS buffer to remove planktonic bacteria, and then dried in a 60°C oven for 30 minutes to fix the biofilm. 200 μL of 0.1% crystal violet staining solution was added to each well, and after staining at room temperature for 15 minutes, it was rinsed with tap water until no pigment flowed out. After drying again, 30% glacial acetic acid solution was added to dissolve the crystal violet, and the absorbance value was measured at a wavelength of 570 nm on a microplate reader. The absorbance directly reflects the amount of biofilm formed. The experimental results show that if Figure 6As shown in the results, selenium nanoparticles can significantly inhibit the formation of MRSA biofilm. With the increase of selenium nanoparticle concentration, the amount of biofilm formed shows a clear dose-dependent downward trend. At a concentration of 100 μg / mL, the inhibition rate of biofilm formation reaches more than 80%, which shows that selenium nanoparticles not only have a direct bactericidal effect, but can also effectively block the establishment and development of bacterial biofilm, providing new strategies and means for the prevention and treatment of bacterial infections.
[0081] The following provides Example 3 of a specific application scenario of the method provided by the present invention: The research team first established a complete process system for preparing selenium nanoparticles. They selected a 99.8% pure titanium matrix as the starting material. The titanium matrix had a size of 25mm×15mm×2mm and a surface area of 10.5 In the pretreatment stage, the titanium substrate was completely immersed in 450ml of acetone solution, and the ultrasonic cleaning frequency was set to 28kHz and the power density was 3.5W / The immersion time is 13 minutes to ensure that the organic pollutants on the surface are completely removed. Then prepare a mixed polishing liquid with a volume ratio of 1:1, where The concentration is 67%, the HF concentration is 43%, and the total polishing liquid volume is 200ml. The cleaned titanium substrate is placed in the polishing liquid for chemical polishing. The polishing time is strictly controlled to 58 seconds, and the polishing liquid temperature is maintained at 23°C. The strong oxidizing effect of nitric acid and the strong corrosiveness of hydrofluoric acid on oxides are synergistically removed. After chemical polishing, the substrate is immediately rinsed with deionized water with a conductivity of 5.2μS / cm for 8 minutes and air-dried in a clean environment at a relative humidity of 45% and a temperature of 28°C.
[0082] In preparation In the nanotube array stage, the research team used a bipolar electrolytic cell for anodic oxidation. The pretreated pure titanium was used as the anode, 316L stainless steel was used as the cathode, the electrode spacing was precisely set to 3.2cm, and the electrolytic cell was made of polytetrafluoroethylene to avoid interference from impurity ions. The electrolyte used an HF aqueous solution with a volume concentration of 0.65%, and the total volume of the electrolyte was 1000ml. The HF concentration directly affects the diameter and wall thickness parameters of the nanotubes. Anodic oxidation is provided by a regulated DC power supply, the voltage is set to 21V, the oxidation time is 45min, and the electrolyte temperature is strictly controlled at 18°C throughout the process. The current density change is monitored in real time during the oxidation process, and the initial current density is 3.2A / When the oxidation proceeded to the 28th minute, the current density dropped to 0.82A / and tends to be stable, indicating The nanotube array is formed completely and has a uniform structure. After the oxidation is completed, it is thoroughly rinsed with deionized water to remove the residual electrolyte and dried at 85 ° C for 40 minutes to obtain a regular and orderly nanotube array. The nanotube array structure has a tube diameter measurement result of 65-75nm and a tube length of about 2.8μm.
[0083] Electrochemical deposition of selenium nanoparticles is the core step of the entire preparation process. The research team prepared a concentration of mol / L The electrolyte is a water solution with a total volume of 800 ml. A 37% volume concentration of diluted HF water solution is used to accurately adjust the pH value of the electrolyte to 2.3. The acidic environment is conducive to The electrode configuration adopts a three-electrode system to prepare The titanium substrate of the nanotube array serves as the cathode, stainless steel serves as the anode, and a saturated calomel electrode is introduced as the reference electrode to precisely control the deposition potential. The deposition voltage is set to 0.52 V, which is determined based on the standard electrode potential of selenium and can ensure The ions undergo an effective reduction reaction on the cathode surface to generate elemental selenium. The electrolyte temperature is controlled at 26°C, and a magnetic stirrer is used at 150 rpm to maintain the uniformity of the solution to avoid the influence of concentration gradient on the uniformity of deposition. The deposition process adopts an electrochemical kinetic control strategy combining cyclic voltammetry and chronoamperometry. The progress of the deposition process is judged by real-time monitoring of the current density change. Deposition is stopped when the selenium nanoparticle loading reaches 0.52wt%. The loading is accurately calculated by coulometric method. The total deposition time is 168min, and the actual deposited mass of selenium is 0.0923g.
[0084] As shown in Table 1, in order to obtain the best ultrasonic dispersion effect, the research team used the particle swarm optimization algorithm to systematically optimize the ultrasonic parameters.
[0085] Table 1 Particle swarm optimization algorithm parameter settings and dispersion effect evaluation
[0086] According to the optimization results of the particle swarm optimization algorithm in Table 1, the research team loaded selenium nanoparticles The titanium matrix of the nanotube array was placed in 1.5L of deionized water, with the water volume being 18 times that of the matrix, providing ample dispersion space. The ultrasonic equipment was set according to the optimized parameters, with an ultrasonic frequency of 48kHz and a power of 268W. Continuous ultrasonication was performed for 36s followed by a 3s pause, and this cycle was repeated. The total effective ultrasonic time was 15min. A water bath was used for temperature control during the ultrasonic process, and the water bath temperature was precisely controlled at 29°C to prevent overheating from causing oxidation or agglomeration of the nanoparticles. The dispersion effect was evaluated in real time by an online particle size monitoring system, and the final polydispersity index (PDI) was 0.22, far below the preset standard of 0.3, indicating excellent dispersion.
[0087] The centrifugal separation was performed using a high-speed refrigerated centrifuge for gradient separation. The centrifuge model was Sigma 3K30, equipped with an angle rotor. The centrifugal temperature was set at 26°C, the speed was 9800 rpm, and the total centrifugation time was 14 min. The separation process was divided into two stages. The primary separation was performed at 7500 rpm for 6 min. The main purpose was to remove large particle impurities and incompletely dispersed agglomerates. The fine separation was performed at a set speed of 9800 rpm for 8 min to ensure that the selenium nanoparticles in the target particle size range were completely settled. After the centrifugation was completed, the supernatant was carefully removed and the selenium nanoparticle precipitate at the bottom of the tube was collected. Subsequently, a systematic washing and purification was carried out. The precipitate was re-dispersed with deionized water. The dispersion volume was 55% of the original suspension volume. The particles were slightly shaken to redisperse evenly, and the centrifugation was performed again under the same conditions. The washing process was repeated 4 times until the conductivity of the supernatant dropped to 12 μS / cm and the pH value was stabilized in the range of 6.8 to 7.2 to ensure that the residual electrolyte and process impurities were completely removed. After each wash, a sample was taken to test the ion concentration of the supernatant. When When the ion concentration is less than 0.5 mg / L, it indicates that the washing is sufficient.
[0088] Freeze-drying was used to remove residual water from the selenium nanoparticles. The washed wet selenium nanoparticles were transferred to a vacuum freeze dryer and spread in a thin layer onto a pre-chilled polytetrafluoroethylene tray. The spread thickness was controlled to 2.8 mm to ensure uniform drying. The vacuum level in the freeze dryer was set to 3 Pa, and the cold trap temperature was controlled at -45°C to effectively capture sublimated water vapor. The drying process was controlled using a three-stage program. The first stage involved pre-freezing, where the temperature was set at -25°C for 2 hours to completely crystallize the free water in the sample. The second stage involved main drying, where the temperature was slowly raised to -10°C for 8 hours to remove the free water by sublimation. The third stage involved desorption drying, where the temperature was raised to 25°C for 4 hours to completely remove the bound water. Dehydration progress was monitored gravimetrically throughout the drying process. Drying was complete when the difference between two consecutive weighings was less than 0.05% of the total sample weight. After drying, the sample was removed under a blanket of dry nitrogen, resulting in a free-flowing, spherical selenium nanoparticle powder with a moisture content of 0.4% as determined by Karl Fischer spectroscopy.
[0089] Quality control testing was comprehensively evaluated using multivariate characterization techniques. Transmission electron microscopy (TEM) was performed using a JEOL JEM-2100 transmission electron microscope (TEM), with an accelerating voltage of 200 kV and a point resolution of 0.23 nm. During sample preparation, selenium nanoparticles were dispersed in anhydrous ethanol to a concentration of 0.25 mg / ml. After ultrasonic dispersion for 30 s, the particles were added dropwise onto a 200-mesh copper grid and dried naturally at room temperature. High-resolution morphological images were obtained using TEM. The particle size data of 296 particles were measured and statistically analyzed, resulting in a calculated average particle size of 42.8 nm, a standard deviation of 7.6 nm, and a coefficient of variation of 17.8%, meeting the quality standard of less than 20%. The particles were spherical in shape, smooth in surface, well dispersed, and free of obvious agglomeration. X-ray photoelectron spectroscopy (X-ray spectroscopy) was performed using a Thermo Scientific K-Alpha XPS with a monochromated aluminum target X-ray source, an X-ray power of 250 W, and an energy spectrum of 1460.9 eV. The full spectrum scan results of selenium element showed that the peak of Se 3d orbital binding energy appeared at 54.8eV and the peak of Se 3p orbital binding energy appeared at 159.2eV, which were consistent with the standard binding energy values of elemental selenium, confirming that selenium existed in the form of zero-valent elemental substance. The characteristic peak (Se 3d binding energy approximately 58.7 eV) indicates that the product contains extremely low selenium oxide content and a selenium purity of 98.9%. Dynamic light scattering measurements were performed using a Malvern Zetasizer Nano ZS particle size analyzer with a laser wavelength of 633 nm and backscattered detection at a scattering angle of 173°. During sample preparation, selenium nanoparticles were dispersed in ultrapure water at a concentration of 0.08 mg / ml. Ultrasonic dispersion was performed for 1 minute to ensure uniform dispersion. Measurements were performed at 25°C, with eight replicates per sample taken as the average. The hydrodynamic diameter was 44.6 nm, consistent with the transmission electron microscopy results. The polydispersity index (PDI) was 0.21, indicating a uniform particle size distribution. The zeta potential was -18.6 mV, indicating a negative surface charge on the particles, which is beneficial for dispersion stability.
[0090] As shown in Table 2, the research team comprehensively characterized the physical and chemical properties of selenium nanoparticles.
[0091] Table 2 Characterization results of physical and chemical properties of selenium nanoparticles
[0092] As can be seen from Table 2, the prepared selenium nanoparticles meet the preset quality standards in terms of various physical and chemical indicators, and the product quality is stable and controllable. / g, which is beneficial to improving biological activity. X-ray diffraction analysis confirmed that it is an amorphous structure with higher chemical activity.
[0093] The research team then conducted systematic animal experiments to verify the anti-MRSA efficacy of selenium nanoparticles. 8-10-week-old female BALB / c mice weighing 18-22 g were purchased from a laboratory animal center under license number SCXK (Beijing) 2021-0006. All mice were acclimated for one week in an SPF-grade animal room with free access to food and water. The room temperature was 22±2°C, the relative humidity was 55±10%, and the light-dark cycle was 12 hours. The experiments were approved by the Animal Ethics Committee and conducted in strict accordance with the Standards for the Use and Care of Laboratory Animals.
[0094] The MRSA strain used was the highly virulent MRSA-USA300 isolated from a clinic. This strain showed high resistance to a variety of antibiotics, including methicillin, penicillin, erythromycin, and ciprofloxacin. The minimum inhibitory concentration (MIC) values were >256 μg / ml for methicillin, >128 μg / ml for penicillin, 64 μg / ml for erythromycin, and 32 μg / ml for ciprofloxacin. It was only sensitive to vancomycin, with an MIC value of 2 μg / ml. The strain was cultured in TSB medium at 37°C for 18 h, and the bacterial solution concentration was adjusted to CFU / ml was used for infection modeling.
[0095] As shown in Table 3 , the experimental design included 8 different experimental groups, with 12 mice in each group, and a total of 96 mice participated in the experiment.
[0096] Table 3 Group design of the mouse MRSA infection model experiment
[0097] According to the experimental design in Table 3, MRSA infection model was established by intraperitoneal injection, with each mouse intraperitoneally injected with 0.5 ml of CFU MRSA bacterial suspension. Treatment began 24 hours after infection, strictly following the protocol for each group. Selenium nanoparticles were prepared in saline to the appropriate concentration before administration. Ultrasonic dispersion was performed for 2 minutes to ensure uniform dispersion. Preparation and use were immediate to avoid aggregation. Vancomycin was purchased from a pharmaceutical company with a purity >98% and prepared in saline to the therapeutic concentration.
[0098] During the experiment, the general condition of the mice was observed daily, including mental state, activity level, food and water intake, and hair gloss. Weight changes and mortality were recorded. Blood samples were collected on days 1, 3, 5, 7, 10, and 14 after infection to measure changes in inflammatory markers such as white blood cell count, neutrophil percentage, C-reactive protein, and procalcitonin. At the same time, some mice were sacrificed at the corresponding time points, and vital organs such as the liver, spleen, kidneys, and lungs were sterilely removed for bacterial load analysis and histopathological examination.
[0099] As shown in Table 4, the 14-day survival rate of mice in each experimental group showed that selenium nanoparticles had a significant protective effect against MRSA infection.
[0100] Table 4 Statistics of 14-day survival rate of mice in each experimental group
[0101] As can be seen from the results in Table 4, the survival rate of mice in the infection control group was only 25.0%, with an average survival time of 4.8 days. Deaths were mainly concentrated on days 2 to 8 after infection, indicating that the MRSA infection model was successfully established and highly pathogenic. The survival rate of the vancomycin group was 75.0%, showing a certain therapeutic effect. The survival rate of each dose group of selenium nanoparticles increased with increasing dose. The survival rates of the low, medium, and high dose groups were 66.7%, 83.3%, and 91.7%, respectively, showing a clear dose-effect relationship. The survival rate of the combined treatment group reached 91.7%, which was comparable to that of the high-dose selenium nanoparticle group, but the average survival time was slightly prolonged. The survival rate of the preventive administration group was 83.3%, indicating that selenium nanoparticles have a certain effect in preventing MRSA infection.
[0102] Figure 7 A bar chart visually compares the survival rates of mice in eight different experimental groups over a 14-day observation period. The horizontal axis represents the experimental group, including the normal control group, infection control group, vancomycin group, low-dose selenium nanoparticle group, medium-dose selenium nanoparticle group, high-dose selenium nanoparticle group, combination therapy group, and prophylactic administration group. The vertical axis represents the survival rate, expressed as a percentage (%), ranging from 0% to 110%. The graph uses bars of varying grayscale to distinguish between the experimental groups, with the specific survival rate value labeled at the top of each bar. The chart clearly shows that the survival rate of the normal control group was 100%, while that of the infection control group was only 25%, indicating the high lethality of MRSA infection. The survival rate of the vancomycin group was 75%, demonstrating a moderate therapeutic effect. A clear dose-response relationship was observed across the selenium nanoparticle dose groups, with survival rates of 66.7%, 83.3%, and 91.7% in the low-, medium-, and high-dose groups, respectively, demonstrating that selenium nanoparticles have a significant protective effect against MRSA infection, with the effect increasing with increasing dose. The survival rate of the combination therapy group reached 91.7%, comparable to that of the high-dose selenium nanoparticle group. The survival rate of the preventive administration group was 83.3%, demonstrating that selenium nanoparticles have the potential to prevent MRSA infection.
[0103] In order to further evaluate the antibacterial effect of selenium nanoparticles, the research team detected the changes in bacterial load in the organs of mice in each experimental group at different time points after infection.
[0104] As shown in Table 5, the bacterial load test results of the main organs of mice in each group on the third day after infection showed that selenium nanoparticles can effectively reduce the reproduction and spread of MRSA in the body.
[0105] Table 5 Bacterial load detection of organs of mice in each group on day 3 after infection (log CFU / g)
[0106] The results in Table 5 show that bacterial loads in all organs of the infection control group were high, with the spleen showing the highest bacterial load, reaching 7.2 log CFU / g, indicating widespread MRSA proliferation and dissemination. The vancomycin group showed significant reductions in bacterial loads in all organs compared with the infection control group, with the liver bacterial load decreasing from 6.8 to 4.2 log CFU / g, a 38.2% decrease. The antibacterial effect of selenium nanoparticles was dose-dependent across all dose groups. The high-dose group reduced the liver bacterial load to 3.2 log CFU / g, a 52.9% decrease compared with the infection control group, surpassing the vancomycin group. The combination therapy group showed the greatest antibacterial effect, with the lowest bacterial loads in all organs, including the liver, at only 2.8 log CFU / g, a 58.8% decrease compared with the infection control group. The prophylactic group also demonstrated a good preventive effect, with bacterial loads in all organs significantly lower than those in the infection control group.
[0107] Figure 8 A grouped bar chart shows the distribution of bacterial loads in five key organs (liver, spleen, kidney, lung, and blood) of mice in each experimental group on day 3 post-infection. The horizontal axis represents the experimental group (excluding the normal control group, as no bacteria were detected), including the infection control group, vancomycin group, low-dose selenium nanoparticle group, medium-dose selenium nanoparticle group, high-dose selenium nanoparticle group, combination treatment group, and prophylactic group. The vertical axis represents bacterial load, expressed in log CFU / g, ranging from 0 to 8. Five bars of varying grayscale represent different organs, with a legend in the upper right corner. The chart shows high bacterial loads in all organs in the infection control group, with the spleen showing a peak of 7.2 log CFU / g, indicating widespread MRSA proliferation and dissemination. The vancomycin group showed significantly lower bacterial loads in all organs compared to the infection control group, demonstrating antibacterial efficacy. The antibacterial effect of selenium nanoparticles was dose-dependent across all dose groups, with the high-dose group showing significantly lower bacterial loads in all organs than the low-dose group. The combined treatment group had the best antibacterial effect, with the lowest bacterial load in each organ. The preventive medication group also showed a good preventive effect, with bacterial loads in each organ significantly lower than the infection control group.
[0108] In order to evaluate the effects of selenium nanoparticles on the body's immune inflammatory response, the research team detected changes in major inflammatory indicators in the serum of mice in each experimental group.
[0109] As shown in Table 6, the results of serum inflammatory index detection in each group of mice on the 5th day after infection reflected the anti-inflammatory effect of selenium nanoparticles.
[0110] Table 6 Detection of serum inflammatory indicators in mice in each group on the 5th day after infection
[0111] The results in Table 6 show that the serum inflammatory indicators of mice in the infection control group were significantly increased, with the white blood cell count reaching 18.7× / L, an increase of 222% compared with the normal control group; the neutrophil ratio increased to 78.5%, C-reactive protein CRP increased to 45.8mg / L, procalcitonin PCT increased to 8.9ng / ml, and interleukin-6 increased to 286pg / ml, indicating that MRSA infection caused a severe systemic inflammatory response. The inflammatory indicators in the vancomycin group decreased compared with the infected control group, but were still significantly higher than normal levels. The anti-inflammatory effect of selenium nanoparticles in each dose group was dose-dependent, and the white blood cell count in the high-dose group dropped to 9.6× / L, the neutrophil ratio dropped to 41.2%, CRP to 19.5mg / L, and PCT to 2.7ng / mL, all of which were superior to those in the vancomycin group. The combination treatment group had the most significant anti-inflammatory effect, with all inflammatory indicators approaching normal levels. The prophylactic group also demonstrated a good anti-inflammatory effect, with all indicators significantly lower than those in the infection control group.
[0112] Histopathological examination is an important indicator for evaluating the efficacy of drug treatment. The research team conducted detailed pathological analysis of the liver, spleen, kidney, and lungs of mice in each experimental group.
[0113] As shown in Table 7, the histopathological scores of the main organs of mice in each group on the 7th day after infection reflected the protective effect of selenium nanoparticles on infected tissues.
[0114] Table 7 Histopathological scores of organs of mice in each group on day 7 after infection
[0115] Histopathological scoring was performed on a 0-4 scale, with 0 representing normal, 1 representing mild damage, 2 representing moderate damage, 3 representing severe damage, and 4 representing extremely severe damage. Table 7 shows that the infection control group exhibited severe inflammatory damage in all organs. The liver showed extensive inflammatory cell infiltration and hepatocyte degeneration and necrosis; the spleen showed marked congestion and swelling, with lymphopenia; the kidneys showed swelling and necrosis of renal tubular epithelial cells and interstitial inflammation; and the lungs showed diffuse alveolitis and pulmonary edema. The vancomycin group showed some reduction in the severity of organ damage, but moderate inflammation persisted. The tissue protective effect of selenium nanoparticles was dose-dependent across all dose groups. The high-dose group achieved a comprehensive injury score of only 5.5, significantly superior to the vancomycin group's 8.7. The combination treatment group demonstrated the greatest tissue protective effect, with a comprehensive injury score of 4.5 and only mild inflammation in all organs. The prophylactic group also demonstrated good tissue protection, with significantly less damage to all organs compared to the infection control group.
[0116] To evaluate the safety of selenium nanoparticles, the research team conducted a detailed toxicology study. Sixty healthy BALB / c mice were randomly divided into six groups of 10 mice each and given different doses of selenium nanoparticles for acute toxicity testing.
[0117] As shown in Table 8, the results of the acute toxicity test of selenium nanoparticles showed that they had good safety.
[0118] Table 8 Results of acute toxicity test of selenium nanoparticles
[0119] The results in Table 8 show that the median lethal dose (LD50) of selenium nanoparticles is 520 mg / kg, significantly higher than the therapeutic dose of 20 mg / kg, with a safety index of 26, indicating the high safety of selenium nanoparticles. Within the therapeutic dose range (5-20 mg / kg), mice showed no significant toxic reactions, with only a slight decrease in activity at the high dose (100 mg / kg).
[0120] In the long-term toxicity study, 80 BALB / c mice were randomly divided into 4 groups, with 20 mice in each group (half male and half female). The mice were given normal saline, low-dose selenium nanoparticles (5 mg / kg), medium-dose selenium nanoparticles (10 mg / kg), and high-dose selenium nanoparticles (20 mg / kg), respectively. The drugs were administered for 28 consecutive days, and the general condition, weight changes, hematological indicators, serum biochemical indicators and histopathological changes of major organs of the mice were observed.
[0121] As shown in Table 9, the results of the 28-day repeated administration toxicity test of selenium nanoparticles showed that they have good long-term safety.
[0122] Table 9 Main indicators of 28-day repeated administration toxicity test of selenium nanoparticles
[0123] The results in Table 9 show that after 28 days of continuous administration, the main safety indicators of mice in each dose group were not statistically different from those in the control group (P>0.05), indicating that selenium nanoparticles are safe for long-term use within the therapeutic dose range. Histopathological examination revealed no significant organ damage, with only mild hepatocyte vacuolar degeneration observed in the liver of the high-dose group, which was mild and reversible.
[0124] In order to explore the antibacterial mechanism of selenium nanoparticles, the research team conducted an in vitro mechanism study. Transmission electron microscopy was used to observe the morphological changes of MRSA bacteria under the action of selenium nanoparticles. The results showed that selenium nanoparticles can bind to the bacterial cell wall, resulting in the destruction of cell wall integrity, cytoplasm outflow, and bacterial death. Reactive oxygen detection experiments showed that the level of reactive oxygen species in MRSA bacteria increased significantly after treatment with selenium nanoparticles, including superoxide anions, hydroxyl radicals, hydrogen peroxide, etc. These reactive oxygen species attack the bacterial cell membrane lipid bilayer, causing damage to the membrane structure. ATP content detection showed that selenium nanoparticles can significantly reduce the ATP level in MRSA bacteria, indicating that it interferes with the energy metabolism process of bacteria. DNA damage detection showed that the DNA of MRSA bacteria treated with selenium nanoparticles showed obvious breakage and damage, further confirming its bactericidal mechanism.
[0125] The research team also evaluated the pharmacokinetic properties of selenium nanoparticles in mice. After a single intraperitoneal injection of 20 mg / kg of selenium nanoparticles was given to mice, blood was collected at different time points to detect changes in serum selenium concentration. The results showed that the peak concentration Cmax of selenium nanoparticles in the body was 18.5 μg / ml, the peak time Tmax was 2.3 hours, the half-life t1 / 2 was 4.6 hours, and the bioavailability was 78.2%. Tissue distribution studies showed that selenium nanoparticles were mainly distributed in the liver, spleen, and lungs, and the concentration in infected tissues was 2.3 times that of normal tissues, showing good targeting of the infection site. Selenium nanoparticles are mainly metabolized through the liver, and the metabolites include selenate, selenomethionine, etc. About 85% are excreted from the body through urine and feces within 48 hours.
[0126] In order to verify the stability and reproducibility of the selenium nanoparticle preparation process, the research team conducted five batches of continuous preparation verification, preparing 8g of selenium nanoparticle products in each batch.
[0127] As shown in Table 10, the quality control results of 5 batches of selenium nanoparticles products showed good process stability.
[0128] Table 10 Quality control results of 5 batches of selenium nanoparticles
[0129] The results in Table 10 show that the relative standard deviations (RSDs) of the key quality indicators of the five batches of products were all less than 7%, with the RSDs of particle size, selenium purity, and yield being 1.5%, 0.2%, and 0.7%, respectively, demonstrating excellent process reproducibility. The average particle size was stable at 43.3 nm, the PDI value was 0.22, the selenium purity reached 98.7%, the loading was 0.51 wt%, the yield was 76.9%, and the specific surface area was 28.6 / g, all indicators meet the quality standard requirements.
[0130] Traditional treatment of MRSA infections mainly relies on antibiotics such as vancomycin, linezolid, daptomycin, and tigecycline, but these drugs have obvious limitations. Vancomycin is a first-line drug for the treatment of MRSA infections. Although it has good antibacterial activity, its ability to penetrate biofilms is limited, and its therapeutic effect on deep infections and biofilm-related infections is poor. Although linezolid has good tissue permeability, long-term use can easily lead to drug resistance and may cause serious side effects such as thrombocytopenia and peripheral neuropathy. Daptomycin is mainly suitable for skin and soft tissue infections, has limited effect on lung infections, and its high price limits its clinical application. Although tigecycline is effective against multidrug-resistant bacteria, it has obvious gastrointestinal side effects and poor permeability to certain infected sites.
[0131] It should be noted that the variables involved in the present invention are explained in detail as shown in Table 11 below.
[0132] Table 11 Variable Explanation Table
Claims
1. A selenium nanoparticle, characterized in that: The selenium nanoparticles are spherical in structure and have a diameter of about 150 nm. The selenium element exists in the form of elemental selenium. It is prepared by electrochemical deposition on nanotube arrays followed by ultrasonic dispersion.
2. The selenium nanoparticles according to claim 1, characterized in that The loading of the selenium nanoparticles is The selenium nanoparticles are firmly bound to the carrier and are evenly distributed in an amount of 0.3 wt % to 0.8 wt % of the weight of the nanotube array.
3. A method for preparing selenium nanoparticles, for preparing the selenium nanoparticles according to any one of claims 1 or 2, characterized in that: The following steps are included: pre-treating pure titanium with a purity greater than 99%, soaking it in acetone and ultrasonic cleaning to remove surface oil, and then Chemical polishing is performed in a mixed solution of solution and HF solution to remove the natural oxide film on the surface; The pure titanium surface was prepared by anodic oxidation Nanotube arrays, anodic oxidation is carried out in a bipolar electrolytic cell with pure titanium as anode and stainless steel as cathode; electrochemical deposition is used in Selenium nanoparticles are deposited on the nanotube array, treated pure titanium is used as cathode and stainless steel is used as anode, and the electrolyte is Aqueous solution, using dilute HF aqueous solution to adjust the pH value, the electrochemical kinetics principle was used to describe the reduction and deposition behavior of selenium ions; Ultrasonic dispersion was used to deposit Selenium nanoparticles on the nanotube array were dispersed in deionized water, and the particle swarm optimization algorithm was used to optimize the ultrasonic parameter combination to obtain the best dispersion effect. The dispersed suspension was centrifuged, and the precipitate was collected and washed with deionized water. The washed selenium nanoparticles were dried in a vacuum drying oven to obtain spherical selenium nanoparticle products. A game optimization system was constructed with an upper model aiming to maximize the yield of selenium nanoparticles and a lower model aiming to minimize energy consumption.
4. The method for preparing selenium nanoparticles according to claim 3, characterized in that: The chemical polishing step is specifically carried out at a volume ratio of 1 to 1. Chemical polishing is performed in a mixed solution of the solution and the HF solution for 55 to 65 seconds to remove the natural oxide film on the surface, and the surface is then removed and cleaned with deionized water and dried for later use.
5. The method for preparing selenium nanoparticles according to claim 4, characterized in that: The anodic oxidation method is used to prepare The nanotube array step is as follows: the power supply is a regulated DC power supply, the voltage is controlled within the range of 18V to 25V, the oxidation time is 30 minutes to 50 minutes, and the electrolyte is an HF aqueous solution with a volume concentration of 0.4% to 0.8%.
6. The method for preparing selenium nanoparticles according to claim 5, characterized in that: The bipolar electrolytic cell refers to an electrolysis device having two electrodes, an anode and a cathode, the electrode materials of which are pure titanium and stainless steel respectively. During the electrolysis process, ions undergo directionally migration under the action of an electric field to form a current loop.
7. The method for preparing selenium nanoparticles according to claim 6, characterized in that: described Nanotube array refers to a titanium dioxide film with a regular tubular structure formed on the titanium surface by anodization. The tube diameter range is related to the anodization voltage and time, and the tube wall thickness is determined by the electrolyte concentration.
8. The method for preparing selenium nanoparticles according to claim 7, characterized in that: The steps of the electrochemical deposition method are as follows: the electrolyte has a concentration of mol / L to In the range of mol / L The aqueous solution was prepared by adjusting the pH value to 2 to 3 using a diluted HF aqueous solution with a volume concentration of 35% to 40%. The deposition voltage was controlled in the range of 0.4V to 0.7V, and the selenium nanoparticle loading during the deposition process reached 0.5wt%.
9. Use of selenium nanoparticles in the preparation of a drug for treating methicillin-resistant Staphylococcus aureus, characterized in that: The selenium nanoparticles according to claim 1 or 2 are used to inhibit the growth and reproduction of methicillin-resistant Staphylococcus aureus and destroy its biofilm structure.
10. The use according to claim 9, characterized in that The antibacterial concentration range of the selenium nanoparticles is 10 μg / ml to 100 μg / ml. Within this concentration range, the selenium nanoparticles have no obvious cytotoxicity to bone marrow mesenchymal stem cells and have good biocompatibility.
Citation Information
Patent Citations
Method for preparing medical titanium material with high anti-cancer and antibacterial properties
CN102560598A
Selenium-doped titanium dioxide nanotube array anti-tumor implant for orthopedics department
CN113456896A
Application of functionalized nano-selenium in preparation of anti-wound infection drugs
CN114288319A
Selenium-doped titanium-based metal as well as preparation method and application thereof
CN116271229A
Antibacterial high-dispersity nano-selenium particles and preparation method thereof
CN116281882A
Cited By
Semiconductor selenium nanoparticle low-temperature preparation method and light absorption application thereof
CN122059381A